2022
DOI: 10.3390/ijerph20010082
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cigarettes and Waterpipe Smoking among Jordanians, Refugees, and Migrants in Jordan and Its Associated Factors: A Secondary Data Analysis

Abstract: Smoking is a major public health threat resulting in increased morbidity and mortality. This study aimed to determine the prevalence of current smoking among different adult populations in Jordan, including Jordanians, refugees, and migrants and determine the factors associated with smoking. A cross-sectional survey was conducted during the period of June–September 2021 among Jordanians, Syrian refugees (both urban and camp refugees), and migrants living in four governorates in Jordan, including Amman, Zarqa, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Smoking, for example, increases the risk of developing ASCVD [ 39 ]. Our findings may be corroborated by the staggeringly high rate of Jordanian male smokers (54.9%) compared to females (8.3%) [ 40 ].…”
Section: Discussionsupporting
confidence: 67%
“…Smoking, for example, increases the risk of developing ASCVD [ 39 ]. Our findings may be corroborated by the staggeringly high rate of Jordanian male smokers (54.9%) compared to females (8.3%) [ 40 ].…”
Section: Discussionsupporting
confidence: 67%
“… 26 , 32 , 33 One possible justification for the increased transformation to AML among males is higher smoking rates. 34 - 36 Third, we found that SF levels influence OS of non-AML MDS patients. Patients with MDS with baseline SF levels >1,000 μg/L had poorer prognosis when compared with those with levels <1,000 μg/L.…”
Section: Discussionmentioning
confidence: 74%
“…Pharmacogenomics variations, lifestyle and environmental factors, prevalent comorbidities, and healthcare access disparities can modulate treatment responses ( 43 , 44 ). In Jordan, the high prevalence of smoking, particularly among males ( 2 ), and the younger age at lung cancer diagnosis may result in distinct disease profiles, influencing treatment outcomes. Our study showed that 87% of the patients were males, 88% were smokers or ex-smokers, and the median age of lung cancer diagnosis was 59.…”
Section: Discussionmentioning
confidence: 99%
“…In males, it is the second most prevalent type of cancer and the primary cause of cancer-related mortality, accounting for 22.4% of all cancer deaths among men ( 1 ). The smoking prevalence in Jordan reaches up to 51% ( 2 ) and the average age for lung cancer diagnosis was reported as 63.8 years ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation